2013
DOI: 10.1113/jphysiol.2013.260588
|View full text |Cite
|
Sign up to set email alerts
|

The spinal reflex cannot be perceptually separated from voluntary movements

Abstract: Key points• Voluntary motor commands and spinal reflexes both produce body movements that activate sensors located in the muscles, joints, tendon and skin.• It is unknown whether perceptions generated by the sensory inputs from voluntary movements can be distinguished from perception of inputs due to spinal reflexes. Surprisingly, the perception of reflexes remains largely unaddressed.• Knee-jerk reflexes were perceived accurately on the basis of proprioceptive inputs alone, but perception was poorer when volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Others, who showed no somatosensory defects during the test, displayed an exaggerated stretch reflex at the knees and ankles when in the sitting position. Ghosh and Haggard (2014) reported that sensory perception inputs generated as a result of voluntary movements were indistinguishable from those leading to spinal reflexes. Therefore, individuals with hemiparesis might be unable to utilize appropriate somatosensory information during STS movements due to adjustments made by the exaggerated stretch reflex.…”
Section: Discussionmentioning
confidence: 99%
“…Others, who showed no somatosensory defects during the test, displayed an exaggerated stretch reflex at the knees and ankles when in the sitting position. Ghosh and Haggard (2014) reported that sensory perception inputs generated as a result of voluntary movements were indistinguishable from those leading to spinal reflexes. Therefore, individuals with hemiparesis might be unable to utilize appropriate somatosensory information during STS movements due to adjustments made by the exaggerated stretch reflex.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness of reflexive movements has rarely been studied. Isolating the motor commands of these movements, and determining how they contribute to action awareness is difficult, because of their rapid onset, short duration, and close interaction with afferent signals (Ghosh and Haggard, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In normal circumstances, many movements include both a postural and a voluntary goal-directed component. These two components are controlled by quite different mechanisms, but may nevertheless be experienced as a single event (Gurfinkel et al, 1989 ; Ghafouri et al, 1998 ; Ghosh and Haggard, 2014 ). In contrast, in the Kohnstamm aftercontraction, a postural component is experienced in isolation, without any voluntary component.…”
Section: Introductionmentioning
confidence: 99%
“…Isolating the motor commands of other involuntary reflexes, and determining how they contribute to action awareness is difficult because of their rapid onset, short duration, and close interaction with afferent signals (Ghosh and Haggard 2014 ). The Kohnstamm phenomenon does not suffer from this problem.…”
Section: Introductionmentioning
confidence: 99%